Blended Learning Voice: Students’ Perceptions Of Mid Transitioning Into Digital Needs Of Academic Reading - Lilies Youlia Friatin; Etika Rachmawati; Ratnawati Ratnawati (STAI Miftahul Ula Nganjuk, 2017)
Blended learning is one of the e- learnings to be concerned its improvement and it can not be apart from the digital learning practices. Moreover, the application of blended learning itself is such of educational innovation in the 21st century era not only in Indonesian setting but also in the worldwide spread. In fact, the deployement of blended learning which is covered by e-learning in Indonesia is not good enough in higher education setting. The present study investigated students’ perception of applying it in an academic reading class as part of demand in digital era. The descriptive study was employed to analyze the students’ questionnaire toward the application of blended learning during classroom practices with the 30 participants took part in the research. The students’ positive responses and interpretation from students revealed of implementation of it though some troubles occured during teaching and learning process. From the result of the data, it indicates that blended learning can be one of the educators’ choices of classroom practices in order to improve the quality of higher education and it provides innovation of education in digital era. The study provides the limitations and pedagogical suggetions.